Addendum: Improving learning performance in physical education through video-based presentations (VBP) approach - Carla Jobelle Culajara (Physical Education and Sports: Studies and Research, 2025)
This addendum provides additional statements on ethical approval, informed consent, data availability, and AI disclosure to enhance transparency and align the original article with current international publication standards. These updates do not affect the results, interpretation, or conclusions of the original publication.